2017
DOI: 10.18632/oncotarget.15664
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in human telomerase reverse transcriptase (hTERT) gene, gene- gene and gene-smoking interaction with susceptibility to gastric cancer in Chinese Han population

Abstract: AimsTo investigate the association of telomerase reverse transcriptase (TERT) gene polymorphisms and additional gene-gene and gene- environment interaction with gastric cancer (GC) risk.ResultsGC risk was significantly higher in carriers of G allele of rs2736100 than those with TT genotype (TG+ GG versus TT), adjusted OR (95%CI) =1.68 (1.26-2.17), and higher in carriers of G allele of rs2853669 than those with AA genotype (AG+ GG versus AA), adjusted OR (95%CI) = 1.72 (1.19-2.33). We also found that interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Hashemi et al sug-gested that the hTERT rs2736098 variant influence the risk of BC in an Iranian population in southeast Iran (20). Zhang et al found that G allele of rs2736100 and G allele of rs2853669 in TERT gene, interaction between rs2736100 and smoking, and haplotype containing the rs2736100-G and rs2736109-A alleles were all associated with increased gastric cancer risk (21). Both of these two studies disagree with our findings.…”
Section: Resultscontrasting
confidence: 91%
“…Hashemi et al sug-gested that the hTERT rs2736098 variant influence the risk of BC in an Iranian population in southeast Iran (20). Zhang et al found that G allele of rs2736100 and G allele of rs2853669 in TERT gene, interaction between rs2736100 and smoking, and haplotype containing the rs2736100-G and rs2736109-A alleles were all associated with increased gastric cancer risk (21). Both of these two studies disagree with our findings.…”
Section: Resultscontrasting
confidence: 91%
“…Meta-analysis results. Based on the inclusion criteria, a total of 17 studies from 14 previously published articles (15,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) along with the present study results were analyzed for the association between the TERT rs2583669 polymorphism and cancer susceptibility; this included 9,537 cancer cases and 12,370 controls (Table V). By pooling all the previous studies, a statistically significant association between the TERT rs2583669 polymorphism and cancer risk was identified (dominant model: Pooled OR=1.09; 95% CI, 1.03-1.16; P=0.004; Fig.…”
Section: Frequency Of Rs2853669 In South Indian Cervical Cancermentioning
confidence: 99%
“…The carcinogenic effect of tobacco smoke on various organs is well recognized, and it accounts for about 50% increase in GC risk . Previously, lots of studies have investigated the interaction between other genes and smoking on GC, including TNF, Exo1, CYP1A1, IL‐10, ERCC8, GSTP1, and hTERT . They all suggest genetic effects of gene polymorphisms on gastric carcinogenesis can be exacerbated by cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Previously, lots of studies have investigated the interaction between other genes and smoking on GC, including TNF, Exo1, CYP1A1, IL-10, ERCC8, GSTP1, and hTERT. [23][24][25][26][27][28][29] They all suggest genetic effects of gene polymorphisms on gastric carcinogenesis can be exacerbated by cigarette smoking. Here, the interactions of PGC rs9471643 and lnc-C6orf-132-1 rs7749023/ rs7747696 on AG risk could also be affected by smoking, although the mechanism has not been understood.…”
Section: Discussionmentioning
confidence: 99%